Trade in carbon and the effectiveness of carbon tariffs - Christoph Böhringer; Jan Schneider; Emmanuel Asane-Otoo (University of Oldenburg, Department of Economics, 2016)
Carbon-based import tariffs are discussed as policy measures to reduce carbon leakage and increase the global cost-effectiveness of unilateral CO2 emission pricing. We assess how the potential of carbon tariffs to increase cost-effectiveness of unilateral climate policy depends on the magnitude and composition of carbon embodied in trade. For our assessment, we combine multi-region input-output (MRIO) analysis with computable general equilibrium (CGE) analysis based on data from the World Input-Output Database (WIOD) for the period 1995 to 2007. The MRIO analysis confirms that carbon embodied in trade has sharply increased during this period. Yet, the CGE analysis suggests that the effectiveness of carbon tariffs in reducing leakage and improving global-cost effectiveness of unilateral climate policy does not increase over time, whereas the potential to shift the economic burden of CO2 emissions reduction from abating developed regions to non-abating developing regions increases substantially.
Keywords: Q58; D57; D58; 330; carbon tariffs; unilateral climate policy; computable general equilibrium